Times of upheaval : four medievalists in twentieth-century Central Europe conversations with Jerzy Kłoczowski, János M. Bak, František Šmahel, and Herwig Wolfram - Rychterová, Pavlína; Klaniczay, Gábor; Kras, Paweł; Pohl, Walter, 1953- (Central European University Press, 2019)
"The volume unites conversations with four masters of Medieval Studies from east-central Europe: János Bak from Hungary, Jerzy Kłoczowski from Poland, František Šmahel from the Czech Republic, and Herwig Wolfram from Austria. The interviews made by younger colleagues revealed their engaging life stories. The four academics grew up before and during the war, under Nazi occupation, emerged as young scholars in the difficult post-war period, and, for most of their careers, worked in the shadow of the Iron Curtain, two of them spending most of their lifetimes under communist regimes. The conversations focus on ways in which open-minded young intellectuals became medieval historians under difficult circumstances, on how they experienced the long shadows of totalitarian regimes with their acute sensitivity for historical change, and how their perceptions of the world around them reflected back on their approach to medieval history. The histories of their nations were broken, most of them ceased to exist and were re-established during their lifetimes, came under foreign domination, were split, or their territories shifted - what did that mean for their identities and patriotic feelings? How can the present be reflected in the distant mirror of the medieval past? In this book, the four masters reflect about their lives sharing numerous observations, anecdotes, and experiences"--